Juvenile form of alexander disease caused by a previously undescribed mutation in the GFAP gene. a case report - A. I. Pavljuchkova; A. S. Kotov (Русский журнал детской неврологии)
Alexander disease is a form of leukoencephalopathy caused by mutations in the GFAP gene. There are three forms of the disease: infant, juvenile and adult. We present the clinical case of a patient born in 2004 (16 years old) with a debut of the disease at the age of 4 years with complex ticks. further neurological symptoms progressed and appeared atactic gait, intention tremor by performing coordination tests, muscle hypotension, decreased tendon reflexes, nasal voices, and behavior changes.Magnetic resonance imaging revealed changes in the white matter of both frontal lobes. An analysis was made of 59 genes of the panel “Leukodystrophy/leukoencephalopathy” by the method of mass parallel sequencing on the Ion S5. A mutation of the GFAP gene (Nm_002055), 4 exon c.758C>A, p.ALA253Asp in a heterozygous state, not described in Human Gene mutation Database, was detected. The patient was confirmed to have a diagnosis of Alexander disease. According to tractography, a decrease in the number of fibers in the frontal lobes was found.The patient is currently receiving symptomatic treatment.